Crime and deviance - Lawson, Tony, 1950-; Heaton, Tim, 1965- (Basingstoke ; New York : Palgrave Macmillan, 2010)
From surveillance to terrorism and green crime to state crime, this exciting new edition offers an updated survey of key areas in the sociology of crime and deviance. Analysis of recent studies and accessible theory is combined with a variety of activities to provide an invaluable introduction to this popular topic for all students of sociology --Provided by publisher.
Introducing the sociology of crime and deviance -- Crime statistics -- Sociocultural explanations of crime and deviance -- Interactionist explanations of crime and deviance -- Conflict explanations of crime and deviance -- Realist explanations of crime and deviance -- Crime, deviance and ethnicity -- Crime, deviance and gender -- Criminal justice and the victims of crime.
Includes bibliographical references (p. 299-333) and index.
Keywords: Crime -- Sociological aspects; Criminology; Deviant behavior